Durable lesion formation while avoiding esophageal injury during ablation of atrial fibrillation: Lessons learned from late gadolinium MR imaging. (1st February 2018) - Chelu, Mihail G.; Morris, Alan K.; Kholmovski, Eugene G.; King, Jordan B.; Kaur, Gagandeep; Silver, Michelle A.; Cates, Joshua E.; Han, Frederick T.; Marrouche, Nassir F.
Abstract: Introduction: Adequate catheter/atrial tissue contact is critical for lesion formation during radiofrequency (RF) ablation of atrial fibrillation (AF). Late gadolinium enhancement magnetic resonance imaging (LGE‐MRI) is a unique tool for the evaluation of lesion formation and detection of acute esophageal injury. Methods: LGE‐MRIs were obtained prior, within 24 hours of, and at 115 ± 62 days after first AF ablation in 36 patients. The Visitag module of CARTO3 was used to collect contact force (CF) and duration from a CF sensing ablation catheter for each registered ablation point. The minimum CF resulting in permanent lesions was determined. Esophageal enhancement detected by acute LGE‐MRI was classified as mild, moderate, and severe. The CF resulting in esophageal enhancement was determined. Results: A total of 4, 642 registered ablation tags at 50 W power were analyzed. The mean RF duration (5.9 ± 3.7 vs. 5.6 ± 3.2 seconds, P < 0.05), CF (11.5 ± 5.6 vs. 10.9 ± 5.4 g, P < 0.001), and force time integral (FTI) (67.3 ± 54.5 vs. 62.2 ± 52.7 gs, P < 0.01) were significantly higher between ablation tags with and without associated LGE‐MRI detected scar. The mean CF (15.7 ± 6.1 vs. 12.6 ± 5.9 g, P < 0.05, n  =  17 patients) in areas of esophageal enhancement was greater than areas without. Conclusion: Left atrial short duration ablation lesions with a CF greater than 12 g are more likely to be associated with permanent lesion formation. Ablating on top of the esophagus, CF less than 15 g would help minimize esophageal wall injury.